Perceived barriers to physical activity and abdominal obesity in university students from Colombia (2016)
Objective: To evaluate the relationship between self-report barriers associated with the practice of the physical activity (PA) and the presence of abdominal obesity in a university students’ sample of Colombia. Methods: A cross-sectional study was carried out during 2013, involving 5,921 healthy subjects aged 18 to 30 years old (3,348 men) from three cities in Colombia. Waist circumference (WC) was measurements as obesity abdominal indicator. The reference criteria for the analysis comes from cut-off points proposed by international reference. It was applied the questionnaire “Barriers to Being Active Quiz” (BBAQ -21) which was validated in Colombia. Prevalence ratios (PR) were calculated between each domain of the questionnaire and the classification of abdominal obesity. Results: The prevalence of abdominal obesity was 10.4 % with gender differences (7.3% men vs. 12.6% women, p less than 0.01). Overall, the “lack of time”, the “social influence” and “lack of skills” were the most prevalent barriers to end the practice of PA in the group of respondents with abdominal obesity. When comparing healthy students with WC, the RP to present abdominal obesity was higher in the group women than men in the domains of the questionnaire BBAQ -21 “ lack of time” (RP = 1.33 [95% CI 1.11 to 1.60]) vs. (OR = 1.14 [95% CI 1.03 to 1.26]) and “lack of resources” (RP = 1, 93 [95% CI 11.67 to 2.24]) vs. (OR = 1.83 [95% CI 1.68 to 1.99]), respectively. Conclusion: Participants with abdominal obesity perceived more barriers to practice physical activity in Colombia university student’s. © 2016, Grupo Arán Ediciones. All rights reserved.